(untitled) (Research, Society and Development, 2021)
The present work was designed with the objective of characterizing the current studies on the use of essential oils in the treatment of neuralgia in an animal model. It is a systematic review of the literature, where the bibliotegraphic survey was carried out in December 2019, through electronic research, consulting the Medline-PubMed, LILACS, Scopus and Web of Science databases. The present study identified 338 articles. 324 were removed, and 14 articles were selected after the established inclusion and exclusion criteria. All articles selected were in the English language, among them 14 were carried out in Brazil with research using extracts, isolated or complexed essential oils. This systematic review suggests that the natural compounds found have therapeutic potentials for the treatment of neuralgia conditions.